Development of a Mobile Electrical Installation for Destroying Weeds - N. T. Toshpulatov (Zien Journals, 2024)
The article provides scientific and technical information about the types, distribution and harmful effects of weeds on crop yields, information analysis of scientific, technical and research works on the effectiveness of existing technologies used in clearing contaminated crop areas from weeds. As a solution to the problem, an environmentally friendly, highly efficient electrical technology is proposed, based on the destruction of weeds with discharges of electric pulse current
Keywords: cultivated plants; productivity; weeds; electrode